A test of the compensatory mortality hypothesis in mountain lions: A management experiment in West‐Central Montana. Issue 5 (2nd June 2014) - Robinson, Hugh S.; Desimone, Richard; Hartway, Cynthia; Gude, Justin A.; Thompson, Michael J.; Mitchell, Michael S.; Hebblewhite, Mark
ABSTRACT Mountain lions (Puma concolor) are widely hunted for recreation, population control, and to reduce conflict with humans, but much is still unknown regarding the effects of harvest on mountain lion population dynamics. Whether human hunting mortality on mountain lions is additive or compensatory is debated. Our primary objective was to investigate population effects of harvest on mountain lions. We addressed this objective with a management experiment of 3 years of intensive harvest followed by a 6‐year recovery period. In December 2000, after 3 years of hunting, approximately 66% of a single game management unit within the Blackfoot River watershed in Montana was closed to lion hunting, effectively creating a refuge representing approximately 12% (915 km2) of the total study area (7, 908 km2). Hunting continued in the remainder of the study area, but harvest levels declined from approximately 9/1, 000 km2 in 2001 to 2/1, 000 km2 in 2006 as a result of the protected area and reduced quotas outside. We radiocollared 117 mountain lions from 1998 to 2006. We recorded known fates for 63 animals, and right‐censored the remainder. Although hunting directly reduced survival, parameters such as litter size, birth interval, maternity, age at dispersal, and age of first reproduction were not significantly affected. Sensitivity analysis showed that female survival and maternity were most influential on population growth. Life‐stage simulation analysis (LSA) demonstrated the effect of hunting on the population dynamics of mountain lions. In our non‐hunted population, reproduction (kitten survival and maternity) accounted for approximately 62% of the variation in growth rate, whereas adult female survival accounted for 30%. Hunting reversed this, increasing the reliance of population growth on adult female survival (45% of the variation in population growth), and away from reproduction (12%). Our research showed that harvest at the levels implemented in this study did not affect population productivity (i.e., maternity), but had an additive effect on mountain lion mortality, and therefore population growth. Through harvest, wildlife managers have the ability to control mountain lion populations. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.